Evaluating the rheological properties and ageing resistance of waste PET-modified bitumen binder - Mashaan, Nuha; Chegenizadeh, Amin; Nikraz, Hamid (Penerbit Universiti Kebangsaan Malaysia, 2021)
Reusing waste plastic can significantly contribute to saving the environment from further pollution and the economy from extra expenses. Waste plastics have a vital role in the current asphalt applications. Trial sections of roads made with waste plastic modified asphalt during 2019 in Australia, highlighted the significant importance of laboratory assessments; however, they are yet to be conducted. This study investigates the impact of using local waste Polyethylene Terephthalate (PET) plastic in bitumen binder class C320, which is a common bitumen type used for local road surfacing in Australia. The evaluation of numerous contents of waste PET modified bitumen is carried out before and after ageing conditions. Dynamic Shear Rheometer (DSR), Rolling Thin Film Oven (RTFOT) and Pressure ageing Vessel (PAV) tests were utilised to examine the rutting, fatigue, and ageing of bitumen binder. The results displayed that the use of waste plastics results in enhanced rutting and ageing resistances. Based on DSR results, bitumen samples modified with waste PET display improved performance in terms of rising the complex shear modulus and reducing the bitumen’s susceptibility to deformation at high temperatures. Furthermore, 8% of waste PET increases the fatigue cracking resistance as it shows a low fatigue factor. Further rutting and fatigue tests on asphalt mixtures samples are recommended to better understand the mechanical properties of waste PET plastic on modified C320 asphalt mixtures.